Unguarded Recursion on Coinductive Resumptions - Goncharov, Sergey; Rauch, Christoph; Schröder, Lutz (Mathematical Foundations of Programming Semantics XXXI, MFPS 2015, 2015)
We study a model of side-effecting processes obtained by adjoining free operations to a monad modelling base effects by means of a cofree coalgebra construction; one thus arrives at what one may think of as types of non-wellfounded side-effecting trees, generalizing the infinite resumption monad. Types of this kind have received some attention in the recent literature; in particular, it has been shown that they admit guarded iteration. Here, we show that they also admit unguarded iteration, i.e. form complete Elgot monads, provided that the underlying base effect supports unguarded iteration.
Keywords: recursion; coalgebra; coinduction; complete Elgot monad; resumptions